DIGITAL TRANSFORMATION AS THE MAIN MEANS OF SMART CITY IMPLEMENTATION - Benny Ranti; K.P. Suharyono S.Hadiningrat; Yosi Widhayanti (JIPOWER : Journal of Intellectual Power, 2024)
Digital Transformation is the process of integrating digital technology in all business areas in an organization. Implementing digital transformation is deemed necessary to optimize performance, change business processes to be more efficient and improve services to users. Smart City Development is an effort by local governments to speed up services to the community, improve the economy, optimize existing budgets and resources, by utilizing information technology (IT). Smart City development will connect, monitor and control various existing resources in the city to maximize services to its citizens, improve community welfare, increase regional income and the community economy as well as collaborate with various parties to support the city's progress. There are 6 (six) indicators of Smart City success, namely Smart Government, Smart Economy, Smart environment, Smart Living, Smart People, and Smart Mobility. This indicator is used as a measure of success. In planning the development of a Smart City, it is necessary to define the vision/mission of a Smart City, determine who the stakeholders are (Village Government, Community, Institutions and partners/third parties) and their needs. The next stage is creating a blueprint for Smart City development and creating a roadmap. Build a Smart City ecosystem to support Smart City development and need to develop KPIs (Key Performance Indicators) to measure the level of success of Smart City implementation. In its development, digital technology is used as the main means of Smart City development to encourage the acceleration and success of Smart City development. This research uses qualitative methods and literature studies to provide recommendations for Smart City development plans and their stages.